2020
DOI: 10.1186/s13058-020-01263-0
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic adverse events following palbociclib dose reduction in patients with hormone receptor–positive/human epidermal growth factor receptor 2–negative advanced breast cancer: pooled analysis from randomized phase 2 and 3 studies

Abstract: Background: Palbociclib improves outcomes for women with hormone receptor-positive/human epidermal growth factor receptor 2-negative advanced breast cancer (HR+/HER2− ABC). Dose reductions are recommended for the management of hematologic toxicities. A previous pooled analysis from the PALOMA clinical trials showed that 36.9% of patients required dose reduction, predominantly during the first 6 months of treatment and with decreasing frequency during subsequent 28-day treatment cycles (C). Previous data have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
2
22
0
1
Order By: Relevance
“…Neutropenia is a known, common, and potentially serious AE associated with palbociclib and all CDK4/6 inhibitors [1, 18, 19]. However, dose reductions, dosing interruptions, or cycle delays of palbociclib have been shown to effectively manage neutropenia without compromising the benefits of palbociclib plus ET combination therapy [20–22]. Findings from a recent analysis of data pooled from the three PALOMA studies showed that reducing palbociclib dose decreased the frequency and severity of neutropenia regardless of patients’ ethnicity, body mass index, or age [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutropenia is a known, common, and potentially serious AE associated with palbociclib and all CDK4/6 inhibitors [1, 18, 19]. However, dose reductions, dosing interruptions, or cycle delays of palbociclib have been shown to effectively manage neutropenia without compromising the benefits of palbociclib plus ET combination therapy [20–22]. Findings from a recent analysis of data pooled from the three PALOMA studies showed that reducing palbociclib dose decreased the frequency and severity of neutropenia regardless of patients’ ethnicity, body mass index, or age [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, dose reductions, dosing interruptions, or cycle delays of palbociclib have been shown to effectively manage neutropenia without compromising the benefits of palbociclib plus ET combination therapy [20–22]. Findings from a recent analysis of data pooled from the three PALOMA studies showed that reducing palbociclib dose decreased the frequency and severity of neutropenia regardless of patients’ ethnicity, body mass index, or age [20]. Importantly, a landmark analysis of data from PALOMA‐2 demonstrated that PFS in patients receiving palbociclib plus letrozole was similar between those whose dose was reduced and those who did not have their dose reduced [22].…”
Section: Discussionmentioning
confidence: 99%
“…50 In our study, lower BMI correlated with higher rates of neutropenia, which was also seen in a recent pooled analysis of two trials testing palbociclib. 53 Perhaps, besides interethnic variabilities, differences in BMI could be one of the mechanistic reasons why Asian patients present higher neutropenia rates with these CDK 4/6 inhibitors. A possible explanation for the lower neutropenia rates in overweight/obese patients could refer to the fact that higher blood neutrophil counts might be a potential inflammatory biomarker of overweightness/obesity, as already shown in non-cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many pooled‐analyses of PALOMA trials have been performed to focus on dose reduction patterns. In the group of patients that need dose reduction in PALOMA trials, there are more Asian women, the mean weight is lower, and basal neutrophil count is slightly lower than in no‐reduction group 5 . However, dose reduction does not appear to impact on survival outcomes in any post hoc analysis 6,7 …”
Section: Figurementioning
confidence: 99%